Abdominal obesity: The cholesterol of the 21st century? - Després, Jean-Pierre (Pulsus Group Inc, 2008)
Cardiovascular disease (CVD) is a leading cause of morbidity and death in many countries worldwide. With the help of epidemiological, metabolic and clinical studies conducted over the past decades, the key factors contributing to the development of CVD have been identified. In this regard, several modifiable (hypertension, smoking, elevated cholesterol or low-density lipoprotein-cholesterol concentrations, reduced levels of high-density lipoprotein-cholesterol, type 2 diabetes) and nonmodifiable (age, sex, genetic predisposition) CVD risk factors have been recognized. Although better acute care and chronic pharmacological management have contributed to reduce CVD mortality, CVD morbidity remains very high. It has been proposed that this situation could be the consequence of the evolving landscape of CVD risk factors, which include, among others, poor nutritional habits and a reduction in physical activity contributing to the epidemic of obesity sweeping the world. However, obesity is heterogeneous both in terms of its etiology and its metabolic complications. Body fat distribution, especially visceral adipose tissue accumulation, has been found to be a major correlate of a cluster of diabetogenic and atherogenic abnormalities that has been described as the metabolic syndrome. The importance of abdominal obesity in association with the development of CVD and type 2 diabetes has been recognized in several studies, beyond the contribution of overall obesity. Additional evidence also suggests that the CVD risk related to the hyperglycemic state observed in subjects with the metabolic syndrome or type 2 diabetes is largely explained by the high prevalence of the metabolic complications of abdominal obesity. Although the presence of the metabolic syndrome clearly increases CVD risk, its clinical diagnosis is not sufficient to classify a patient at high risk for a cardiovascular event because attention must also be paid to the presence of traditional risk factors in the calculation of global CVD risk. The additional information provided by the metabolic syndrome to the risk attributed to traditional risk factors in the calculation of global CVD risk has been defined as global cardiometabolic risk. The fight against abdominal obesity as a major cause of CVD morbidity and mortality will require major societal changes and the involvement of dieticians, kinesiologists and behaviour modification specialists in clinical practice to reshape our physical activity and dietary habits. Finally, the early prevention of overweight/obesity/abdominal obesity in children, starting as early as conception, and the identification of key drivers of unhealthy nutritional and sedentary behaviours are the cornerstone of a successful comprehensive plan to fight CVD morbidity.